The Street-Level Bureaucracy Implementation in Public Service in Villages in Indonesia - Leo B. Barus (Journal of Public Administration and Policy Issues, 2022)
Corruption cases by law enforcement officials in the village fund budget sector until 2021 have reached 154 cases with a potential state loss of IDR 233 billion. It needs handling which is not solely by law enforcement and/or supervision, but also based on improving public services by using the theory of the street-level bureaucracy. Based on the qualitative study, it is concluded that the implementation of the street level bureaucracy in Indonesia in the context of village public services can be carried out through discretion and relative autonomy through top-down and/or bottom-up services. So as to produce quality, fast, easy, affordable, and measurable service functions that can handle village financial irregularities in Indonesia.